2009
DOI: 10.1016/j.ejpain.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic Pain Acceptance Questionnaire (CPAQ)‐further validation including a confirmatory factor analysis and a comparison with the Tampa Scale of Kinesiophobia

Abstract: Acceptance of pain and distress has lately appeared as an important factor in determining peoples' ability to restore functioning in the presence of chronic pain. Although treatments based on cognitive behaviour therapy are beginning to incorporate acceptance strategies, there is still a lack of reliable and valid instruments to assess relevant processes in such interventions. The Chronic Pain Acceptance Questionnaire (CPAQ) was originally constructed as part of the development of an acceptance oriented treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
105
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 46 publications
(71 reference statements)
15
105
0
4
Order By: Relevance
“…Since the development of the 20-item measure, confirmatory factor analysis (CFA) conducted by Vowles et al [8] found support for the two-factor model (i.e., Activity Engagement and Pain Willingness). A more recent CFA conducted by Wicksell et al [5] also found that the twofactor solution showed adequate fit to the data in a Swedish translation of the measure. However, the fit was significantly improved following the removal of an item.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Since the development of the 20-item measure, confirmatory factor analysis (CFA) conducted by Vowles et al [8] found support for the two-factor model (i.e., Activity Engagement and Pain Willingness). A more recent CFA conducted by Wicksell et al [5] also found that the twofactor solution showed adequate fit to the data in a Swedish translation of the measure. However, the fit was significantly improved following the removal of an item.…”
Section: Introductionmentioning
confidence: 89%
“…The total score, as well as the subscales of pain willingness and activity engagement, predict disability, quality of life, and distress [1]. The CPAQ contributes unique variance to pain disability, anxiety, and depression when considered in the context of factors known to be associated with chronic pain such as self-efficacy, catastrophizing, and fear of (re)injury/movement [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The Chronic Pain Acceptance Questionnaire [CPAQ: 36] is a 20-item likert (0-6) scale, validated in Swedish [63]. The short version with 8-items' has been validated in English [1; 10; 11] and in Swedish [48].…”
Section: Methodsmentioning
confidence: 99%
“…Within this tradition, McCracken and colleagues 30 started research in chronic pain. Research has identified two core constituents of acceptance: a willingness to experience pain, and the engagement into valued-based life activity despite pain 32, 51,53 . The other approach originates from self-regulatory theories, in which disengagement from blocked goals and reengagement into new actions is considered as an adaptive way of coping with life dynamics 1,4,22,38 .…”
Section: Introductionmentioning
confidence: 99%